Mistakes and Сomplications in the Treatment of Patients with Malleolus Factures - Liabakh, A.P.; Kucher , I.V. (TERRA ORTHOPAEDICA, 2020)
Summary. The number of mistakes and complications in the diagnostics and treatment of malleolus fractures is still significant. Objective. The retrospective analysis of mistakes and complications in the diagnostics and treatment of malleolus fractures. Materials and Methods. 385 patients with consequences of malleolus fractures (AO/OTA 44) from March 2000 to August 2020. There were 280 men and 105 women aged 18-87 years. The time from the injury was 3–408 months (on average 29.9±6.8 months). The analysis was carried out according to the recommendations of AO and AUPO “Ukrainian Association of Orthopedists-Traumatologists”. Results. Mistakes in the diagnosis and treatment amounted to 57.4% (221 cases); in 164 cases (42.6%) the severity of initial trauma and the time from the injury were objective factors for the development of deforming arthrosis of stages 3-4. Diagnostic defects took place in 40 cases (10.4%). The unproved conservative treatment was used in 47 cases (12.2%). Defects in surgical technique were noted in 174 cases (45.2%): failure to perform osteosynthesis of the fibula in “С” fractures – 24 cases (6.2%), improper surgical approach – 45 cases (11.7%), improper fixator choice – 45 cases (11.7%), transcutaneous wire fixation as the main osteosynthesis – 14 cases (3.6%), and improper tibiofibular stabilization – 49 cases (12.7%). Malreduction of broken bones in operated on patients was registered in 114 cases. Conclusions. Our results may be useful at the planning of future clinical and epidemiological investigations.